Integral characterizations for the (h, k)-splitting of skew-evolution semiflows - MIHIȚ , Claudia Luminița; MEGAN, Mihail (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
The main aim of this paper is to give integral characterizations for a general concept of (h, k)-splitting for skew-evolution semiflows in Banach spaces. As consequences, criteria for the properties of (h, k)-dichotomy, nonuniform exponential splitting and exponential splitting are obtained. Mathematics Subject Classification (2010): 34D09, 40C10.